1997
DOI: 10.1021/jm960583g
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Substituted Benzofused Macrocyclic Lactams as Zinc Metalloprotease Inhibitors

Abstract: The design, synthesis, and biochemical profile of meta-substituted benzofused macrocyclic lactams are described. The meta-substituted benzofused macrocyclic lactams were designed to have a degree of flexibility allowing the amide bond to occupy two completely different conformations while maintaining sufficient rigidity to allow for strong interaction between enzyme and inhibitor. Using TFIT, a novel molecular superimposition program, it was shown that the meta analogs could be readily superimposed onto our AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The local increased hydrophobicity of Zmp1 compared with the NEP S1 subsite could indicate a higher affinity for inhibitors carrying hydrophobic groups at the P1 site, as observed for ECE-1 (41,42). However, the S1 site leaves the rhamnose moiety of the inhibitor exposed to the solvent and plays a minor role in substrate selectivity, as reported for NEP and ECE-1 (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 72%
“…The local increased hydrophobicity of Zmp1 compared with the NEP S1 subsite could indicate a higher affinity for inhibitors carrying hydrophobic groups at the P1 site, as observed for ECE-1 (41,42). However, the S1 site leaves the rhamnose moiety of the inhibitor exposed to the solvent and plays a minor role in substrate selectivity, as reported for NEP and ECE-1 (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 72%
“…Not surprisingly, therefore, this mild and versatile chemistry has also found some utility for the construction of BMR scaffolds. For example, the bridged benzannulated macrocycle 200 was synthesized starting from amino acid 198 (Scheme 7a) 121 while the benzannulated medium-ring ether (48) was prepared via nucleophilic cleavage of enantiomerically pure 1,2-cyclic sulfamidate 201 with phenol derivative 202, followed by Mitsunobu reaction of 203, which led to the formation of scaffold 204 in 30% overall yield, as shown in Scheme 7b. 122 Another variant of the Mitsunobu reaction was reported to affect the closure of a 13-membered lactone in the presence of supported triphenylphosphine in low yield (10%) but was recently more successful in the formal synthesis of salicylihalamides (206, Scheme 7c).…”
Section: Mitsunobu Reactionmentioning
confidence: 99%
“…This is in agreement with the increased hydrophobicity of the S1 sub-site in ECE-1 and the minor stabilizing role of this sub-site in human NEP, for which both compounds show similar IC 50 values. [42][43][44][45] Extensive studies have shown that there is a clear preference for P1′ residues with large hydrophobic side chains, indicating that the specificity of ECE-1 is essentially ensured by this sub-site. 39 The P1′ residue of phosphoramidon and its interaction with the S1′ sub-site is shown in Fig.…”
Section: Phosphoramidon Sub-site Recognition and Specificitymentioning
confidence: 99%